Idiostyle Specificity and the Image of the Author in the Works of L.S. Petrushevskaya - Yo’ldosheva Dilnozaxon Tojiali qizi (Genius Journals, 2022)
The article is devoted to the issues of scientific interpretations of the term " individual style". Various interpretations of the concept are presented, a brief overview of the individual style . Special attention is paid to the work of L.S.Petrushevskaya. The article is relevant due to the fact that the scientific interpretation of the concept is determined using old Soviet-era cliches. The novelty of this article lies in the study of the term " individual style" in the works of L.S.Petrushevskaya from new angles.
Keywords: Idiostyle; individual style; author's image; author's modality